Minimum Incidence Kanker Had Primer di Yogyakarta - Soeripto, Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
There is a tendency of primary liver cancer between 1970-1973 corresponding to the introduction of liver biopsy in Yogyakarta. Liver cancer had previously been found to be the most frequent tumour in necropsy material in Java. In the series, composed of biopsies only, it accounted for 36.8% of all abdominal cancers biopsied in Yogyakarta in 1973 and is thus more frequent than indicated by the total material covering a 4-year period (1970-1973).Based on the data of the Department of Pathology and population in 1976 by utilizing the formulathe primary liver cancer incidence in 1974 through 1978 is provided.It seems that the minimum incidence of primary liver cancer in Yogyakarta is lower than the incidence in other countries in Asia and AfricaKey Words: liver cancer - cancer registration -incidence of hepatoma - racial predisposition for cancer - viral hepatitis